FRONT OFFICEâ€™S â€œICE BREAKERâ€ WITHIN THE HOSPITALITY INDUSTRY: A TRANSLATION STUDY - Habibah Aini Noor; Ni Made Diana Erfiani (LPPM Universitas Dhyana Pura, 2023)
In the context of the hospitality sector, effective communication at the front desk plays apivotal role in guest satisfaction and overall service quality. This study aims to identify thesubtleties of the linguistic and cultural obstacles encountered at the front desk during thecritical